Complications, disease profile and histological yield from percutaneous renal biopsy under real-time US guidance: A retrospective analysis - M Kruger; E Loggenberg (South African Journal of Radiology, 2011)
Objective. The objective of the study was to evaluate (i) the technique used at Universitas Hospital in comparison with other international centres also performing renal biopsies, (ii) the disease profile in patients undergoing renal biopsies, (iii) the complications experienced during and/or after the procedure, and (iv) the histological yield of the biopsies (amount of nephrons per biopsy taken) using this technique.